Síntese controlada de óxido de grafeno obtida em reator de bancada - Andrade, Carolina Santos de (2020)
Graphene oxide (GO) synthesis on a large scale is a reality, but aspects such as reduction of residues produced, reduction of reagents used, reproducibility with quality control are still factors that need to be explored. Thus, reducing the amounts of oxidizing reagents used while maintaining the same experimental synthesis conditions can be a good strategy to improve production processes in large quantities. Based on this line of thinking, the present work proposes a detailed study of use of different graphite /oxidizing reagents (mG/mROxi) proportions in the GO production, aiming to study their limiting conditions that provides good yield, structural quality and economy. Using the improved Hummers method, three samples containing different masses of graphite (called GO 3.0 g, GO 4.5 g and GO 6.0 g) were produced using a bench reactor to ensure the reproducibility of this process. From a structural and composition point of view, all prepared samples had the same characteristics, such as: degree of oxidation, interplanar distances and ID/IG ratio. However, from the exfoliation process of these samples in liquid phase, morphological and structural differences were verified. Through the AFM analyzes it was possible to observe the majority production of graphene oxide nanoforms containing between 1-5 layers with good structural quality, and lateral size up to 1.5µm for the GO 3.0 g and GO 4.5 g samples. However, in the GO 6.0 g sample, rounded micrometric graphitical sheets were observed, containing specific regions similar to “graphene islands”, however the analyzes obtained by this technique were not conclusive for this sample. Therefore, increasing the amount of graphite from 3.0 g to 4.5 g while maintaining the amount of oxidizing reagents produced materials with physicochemical characteristics similar to those of a commercial sample. Thus, a study detailing of mG/mROxi proportions in a controlled manner can be an efficient strategy for the production of GO with structural quality and scale up.